Equity Risk Incentives dan Corporate Tax Aggresiveness - Rahmi Putri Mulia; Herlina Helmy; Mia Angelina Setiawan (Universitas Negeri Padang, 2019)
This study aims to examine the equity risk incentives relationship with corporate tax aggressiveness. This study uses four proxies to measure corporate tax aggressiveness variables, namely Cash Effectives Tax Rate (CETR), Tax Shelter, Unrecognized Tax Benefits (UTB), and Discretionary Book Tax Differences (DTAX). The equity risk incentives variable is measured using the annual natural total log of compensation of the key management. The study population was manufacturing companies listed on the Indonesia Stock Exchange from 2013 to 2017. The study samples were determined by purposive sampling method so that samples for each CETR, Shelter, UTB and DTAX were obtained were 235, 180, 210 and 205 companies. Based on panel data regression analysis, the results show that 1) Equity Risk Incentive is negatively related to Cash Effectives Tax Rate but not significant, 2) Equity Risk Incentive is positively related to Tax Shelter but not significant, 3) Equity Risk Incentive is negatively related to Unrecognized Tax Benefits not significant, and 4) Equity Risk Incentive is positively related to the Discretionary Book Tax Differences but not significant. The conclusion of this study is that equity risk incentives are not positively related significantly with corporate tax aggressiveness so the hypothesis is rejected.Keywords: Equity Risk Incentives; Tax Aggressiveness